Development of learning media of motorcycle brake light electrical systems for motorcycle business engineering students - Nasrah, Sayni; Miko, Riyandi Mutuah; Safriwardy, Ferri (Universitas Malikussaleh, 2022)
Making this learning media aims to determine the results of the manufacture and feasibility of learning media for electric motorcycle brake lights. This study uses the Research and Development (R&D) method. The subjects used were media experts and material experts consisting of two lecturers and two automotive engineering experts. The object of this research is students and the media of electrical circuits. Data collection techniques in this study used the methods of observation, interviews and questionnaires. The study was conducted at SMK Negeri 7 Lhokseumawe with a periods of 6 months. Based on the results of data analysis carried out, the results of the study are in the form of the potential to make an electrical circuit for a motorcycle brake light system. The validation of learning media in this study obtained the average percentage value of the two validators of media expert I 100% and media expert II 90%. Furthermore, validation of the guidebook obtained the average value of the two validators material expert I 87% and material expert II 82%. In addition, the results of student responses with an average percentage value of 85%. Based on the four validators and student responses, it was shown that the electric motorcycle brake light learning media with the category was very feasible to use.